Fiscal Management in Resource-Rich Countries : Essentials for Economists, Public Finance Professionals, and Policy Makers - Ossowski, Rolando (Washington, DC: World Bank, 2016)
The extractive industries (EI) sector occupies an outsize space in the economies of many developing countries. Policy makers, economists, and public finance professionals working in such countries are frequently confronted with issues that require an in-depth understanding of the sector, its economics, governance, and policy challenges, as well as the implications of natural resource wealth for fiscal and public financial management. The objective of the two-volume Essentials for Economists, Public Finance Professionals, and Policy Makers, published in the World Bank Studies series, is to provide a concise overview of the EI-related topics these professionals are likely to encounter.